2011
DOI: 10.1124/jpet.110.177097
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacologic Specificity of Nicotinic Receptor-Mediated Relaxation of Muscarinic Receptor Precontracted Human Gastric Clasp and Sling Muscle Fibers within the Gastroesophageal Junction

Abstract: Relaxation of gastric clasp and sling muscle fibers is involved the transient lower esophageal sphincter relaxations underlying the pathophysiology of gastroesophageal reflux disease (GERD). These fibers do not contribute tone to the high-pressure zone in GERD patients, indicating their role in pathophysiology. This study identifies some mediators of the nicotine-induced relaxation of muscarinic receptor precontracted gastric clasp and sling fibers. Muscle strips from organ donors precontracted with bethanecho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 43 publications
3
15
0
Order By: Relevance
“…Additionally, sphincter failure is proposed as a hallmark of ongoing injury[17,18,20-23] along with an injurious effect of L-NAME itself[1,5,7,17,18,20,45-51] that overrides previous considerations about NO-sphincter relationships[57] while being unrelated to injurious conditions ( i.e ., in dogs, ferrets and muscle strips[58-60]). In rats that underwent esophagogastric anastomosis and L-NAME therapy, the final drop of pressure within the esophagus at the site of anastomosis on day 4 occurs just prior to death.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, sphincter failure is proposed as a hallmark of ongoing injury[17,18,20-23] along with an injurious effect of L-NAME itself[1,5,7,17,18,20,45-51] that overrides previous considerations about NO-sphincter relationships[57] while being unrelated to injurious conditions ( i.e ., in dogs, ferrets and muscle strips[58-60]). In rats that underwent esophagogastric anastomosis and L-NAME therapy, the final drop of pressure within the esophagus at the site of anastomosis on day 4 occurs just prior to death.…”
Section: Discussionmentioning
confidence: 99%
“…We previously found that nicotine causes relaxation of bethanechol precontracted clasp, sling and LEC muscle strips and that this effect occurs indirectly, by activation of nicotinic receptors on enteric nerves that induces release of multiple relaxing substances. These relaxing substances include nitric oxide (NO) in clasp, sling, and LEC fibers, norepinephrine acting on β ‐adrenoceptors in clasp fibers, and GABA acting on GABA A receptors in sling fibers . The current study was undertaken to characterize the pharmacology of the enteric nerve nicotinic receptors mediating these relaxations of the UGS using currently available nicotinic receptor subtype selective agents.…”
Section: Introductionmentioning
confidence: 99%
“…However, some basic insights have been obtained. In most species and experimental preparations, nicotine causes contraction of stomach, jejunal, and ileal muscles, and relaxation of colonic muscles and lower oesophageal sphincter (Braverman et al, 2011;Murakami et al, 2009;Vural, Ozturk Fincan, Bozkurt, Ercan, & Sarioglu, 2009). At a more integrated level, nAChRs are thought to play a crucial role in ascending reflexes but only a minor role in descending reflexes of the myenteric plexus, whereas in the submucosal plexus, most nAChRs are associated with descending projections (Galligan & North, 2004).…”
Section: The Enteric Nervous Systemmentioning
confidence: 99%